Cover Picture: Selective Ion Exchange in Supramolecular Channels in the Crystalline State (Angew. Chem. Int. Ed. 13/2019). Issue 13 (21st February 2019) - Ichihashi, Katsuya; Konno, Daisuke; Maryunina, Kseniya Yu.; Inoue, Katsuya; Toyoda, Kazuhiro; Kawaguchi, Shogo; Kubota, Yoshiki; Tatewaki, Yoko; Akutagawa, Tomoyuki; Nakamura, Takayoshi; Nishihara, Sadafumi
Abstract : Selective ion exchange in the crystalline state was achieved with Li2 ([18]crown‐6)3 [Ni(dmit)2 ]2 (H2 O)4 as reported by S. Nishihara and co‐workers in their Communication on page 4169 ff. When this crystal was soaked in an aqueous solution containing K + ions, the Li + ions in the crystal were completely exchanged with K + ions through the crown‐ether‐based supramolecular channels. In mixed solutions containing K + and Na + /Li + ions, the Li + ions were selectively replaced by K + ions. The ion exchange induced remarkable changes in the magnetic properties and the ionic conductivity.